ANALISIS POTENSI KELOMPOK WANITA TANI OLAHAN PANGAN DI KABUPATEN BANTUL - Kuswadi Rustam (Politeknik Sawunggalih Aji, 2023)
Food processing groups. in Bantul Regency it is dominated by the Women Farmers Group (KWT). Until now, the number of KWT registered at BKP3 Bantul Regency is 275 KWT, generally they are engaged in local food processing such as traditional food and its preparations. Therefore, it is hoped that the existence of KWT can provide great potential in the agricultural sector and can also support food self-sufficiency in the Bantul Regency Region. However, in its development, KWT has several weaknesses, including: (1) limited market, (2) relatively low quality and not durable, (3) unattractive appearance because the packaging is still simple and not informative, resulting in lack of selling value and competitiveness, therefore it is necessary to analyze the potential of women's groups of processed food farmers in Bantul Regency, with the aim of knowing the potential and identifying problems of KWT food processing in Bantul Regency. The method of determining the research object was carried out purposively (purposive method), namely in the Bantul district in the Food Processing Farmer Women's Group which was recorded at BKP3 Bantul Regency, considering that the majority of active groups that process various food ingredients in Bantul Regency are KWT. Random sampling at several KWTs in seventeen Districts of Bantul Regency. While the determination of respondents is done by random sampling or randomly. The results of the study show that the KWT institution illustrates that members act according to their way but are willing/able to take advantage of the opportunities that exist with diverse backgrounds, both their level of ability, knowledge and personality. It can be seen that the majority of them have actively processed various food ingredients, especially for food sources substitute carbohydrates for rice. Even though KWT capital is relatively small, only around IDR 1,000,000 – IDR 2,500,000 or an average of IDR 2,000,000 for each group, economically, their productivity is high, this can be seen from the amount of production produced in one year, ranging from 1,800 kg – 3,600 kg. kg or an average of 2,750 kg.